6x-2/4=x-2

1 answer

To solve this equation, we need to simplify both sides and isolate the variable.

Starting with the left side:

6x - (2/4)

We can simplify 2/4 to 1/2:

6x - 1/2

Now, let's combine like terms by finding a common denominator:

12x/2 - 1/2

This gives us:

(12x - 1) / 2

Now, equating this to the right side of the equation:

(12x - 1) / 2 = x - 2

To remove the fraction, we can multiply both sides of the equation by 2:

2 * (12x - 1) / 2 = 2 * (x - 2)

This simplifies to:

12x - 1 = 2x - 4

We can now isolate the variable by moving the constant term (1) and the x-term (2x) to one side of the equation:

12x - 2x = -4 + 1

10x = -3

Finally, we divide both sides by 10 to solve for x:

10x/10 = -3/10

x = -3/10